Apamin-Conjugated Alendronate Sodium Nanocomplex for Management of Pancreatic Cancer - Nabil A. Alhakamy; Osama A. A. Ahmed; Usama A. Fahmy; Shadab Md (MDPI AG, 2021)
Pancreatic cancer has a low survival rate and has limited therapeutic options due to the peculiarity of the tumor tissue. Cancer nanotechnology provides several opportunities to resolve such difficulties as a result of the high surface-to-volume ratio of nanostructures. Peptide-drug nanocomplexes have proved to have immense potential in anticancer activity against pancreatic cancer cells. Thus, in the present study apamin (APA) and alendronate sodium (ALS) were combined to form nanocomplexes (APA-ALS-NC) against pancreatic cancer cells. Optimization of ALS, incubation time, and sonication time in terms of particle size of the nanocomplex was carried out. The optimized formulation was evaluated for anticancer activities in pancreatic cancer cells (PANC-1 cells). A Box-Behnken design using ALS, incubation time, and sonication time as independent factors and particle size as the response was chosen to optimize the APA-ALS-NC formulation. The optimized APA-ALS-NC had a particle size of 161.52 ± 8.4 nm. The evaluation of APA-ALS-NC in PANC-1 cells was carried out using various in vitro tests. The IC50 values were determined by MTT assay and found to be 37.6 ± 1.65, 13.4 ± 0.59, and 1.01 ± 0.04 µg/mL for ALS, APA, and APA-ALS-NC, respectively. The higher cytotoxicity activity of APA-ALS-NC was confirmed from the higher percentage of cells in the necrosis phase (apoptosis study) and the G2-M phase (cell cycle study) compared to that of ALS and APA. While the loss of mitochondrial membrane potential was less for APA-ALS-NC, the levels of IL-1β, TNF-α, caspase-3, ROS, IL-6, and NF-kB showed that APA-ALS-NC can significantly enhance apoptosis and cytotoxicity in PANC-1 cells. Moreover, Bax (10.87 ± 1.36), Bcl-2 (0.27 ± 0.02), and p53 (9.16 ± 1.22) gene expressions confirmed that APA-ALS-NC had a significant apoptotic effect compared to ALS and APA. In summary, the APA-ALS-NC had a more significant cytotoxic effect than ALS and APA. The results of the present study are promising for further evaluation in pre-clinical and clinical trials for arriving at a successful therapeutic strategy against pancreatic cancer.